THE IMPLEMENTATION MODEL OF MULTICULTURAL ISLAMIC EDUCATION VALUES IN SHAPING THE HUMANIST-RELIGIOUS ATTITUDES OF SANTRIS AT PESANTRENNURUL JADID, PAITON, PROBOLINGGO - Jazilurrahman Jazilurrahman (Jurnal Ijtihad, 2021)
Pesantren is one of the Islamic educational institutions that implements multiculturalism and has humanist-religious values and the potentials for multicultural awareness. To be able to form the humanist-religious attitude of santri in Islamic boarding schools requires a systematic planning, implementation process and evaluation.This study discusses the phenomenon of the implementation model of the multicultural Islamic education value in shaping the humanist-religious attitude of santri at Pesantren Nurul Jadid in Paiton, Probolinggo. In order to obtain data from the results of the study, qualitative research was conducted with a case study approach. Data collection techniques with participant observation, in-depth interviews, and documentation. The data collection technique was using the snowball sampling technique. The data sources used were primary and secondary, while the data analysis technique used the Miles and Huberman’s model. The results of the field research found that the implementation model of multicultural Islamic education values are integrated intoactivities and learning at Pesantren Nurul Jadid. This research provides theoretical implications instrengthening the theory of value integration and scientific interconnection (Amin Abdullah: 2006).Keywords: multicultural Islamic education; implementation model; humanist-religious attitude;pesantren (Islamic boarding school)